Development Of Bio-Ash Supported Nanocomposites For The Photocatalytic Treatment Of Acid Red 88 And Methylene Blue - Lum, Pei Teng (2018)
To date, the wide scale application of photocatalysis, a new innovative and promising technology for the environmental remediation of textile dye pollutants, is experiencing the technical challenges of particles self-agglomeration and post-separation difficulty. Arising research pertaining to the immobilization of photocatalysts onto different supporting materials have been promoted. Giving insight into the huge generation of agricultural bio-ash and highlighting of their low economical value, the development of a series of bio-ash supported nanocomposites by using simple physical coating and hydrothermal techniques has been attempted. Bio-ash including incense ash (IA), durian shell ash (DSA) and coffee residue ash (CA) was adopted to be the low-cost precursors for the preparation of bio-ash supported SnO2 and ZnO nanocomposites, with different ash impregnation ratio from 1:1 to 1:5. Surface morphology analysis, pore structural measurement, detection of surface functional groups and evaluation of point of zero charge (pHzpc) were carried out. The photocatalytic performance was examined with respect to the batch photocatalytic degradation of Acid Red 88 (AR 88) and Methylene Blue (MB) by varying the operational parameters, catalyst loading, initial dye concentration and irradiation time, and solution pH. Surface morphological studies revealed that the deposition of catalysts onto the surface of different bio-ash was successfully attained. Examination of the porosity development suggested that the capability of bio-ash to improve the overall surface area. Fourier-Transform Infrared Spectroscopy (FT-IR) spectrum ascertained the homogenous deposition of SnO2 and ZnO photocatalysts on the surface of bio-ash. Results illustrated the best photodegradation efficacy was achieved at the optimum catalyst loading of 0.03 g/100 mL for SnO2/CA, 0.04 g/100 mL for SnO2/IA and SnO2/DSA nanocomposites, and 0.40 g/100 mL for ZnO/IA, ZnO/DSA, and ZnO/CA nanocomposites, respectively. Acidic medium favors to the photocatalytic removal of AR 88, while the basic condition prefers to the photodegradation of MB. Increasing initial concentration from 100-500 mg/L for AR 88 and from 50-400 mg/L for MB demonstrated the significant influences on the removal efficacy, and a longer irradiation time was acquired for the complete removal process. Kinetic analysis revealed that the linearity of the photocatalytic plots was well described by the first order model. Reusability test indicated high durability of these newly prepared nanocomposites, with greater than 85% of degradation efficiency even after five regeneration cycles. This study provided a new insight in the preparation of valuable bio-ash supported nanocomposites for the effective purification of textile dye pollutants.